DAMPAK KEBIJAKAN STOCK SPLIT TERHADAP VOLUME PERDAGANGAN SAHAM DAN HARGA SAHAM PERUSAHAAN GO PUBLIC YANG TERDAFTAR DALAM BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2014)
This study aimed to determine differences in the volume of stock trading and stock prices go public companies listed on the Indonesia Stock Exchange (IDX) before and after the period of 2008-2012 policy does stock split.The population used in this study were all listed companies go public in the Indonesia Stock Exchenge (IDX) in the study period 2008-2012 the number of 457 companies. While the sample used in this study were 25 companies that perform public policy go stock split. The sampling technique used was purposive sampling. The analytical tool used in this study are different test (paired sample t test).The results of this study show the first hypothesis there is a difference significant trading volume before and after the stock split. This study also shows the second hypothesis there is a difference significant stock price before and after the stock split.Keywords: stock split, stock trading volume, stock price